2020
DOI: 10.2166/ws.2020.361
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of vegetation change on runoff generation mechanism in the Loess Plateau, China

Abstract: In recent years, the amount of water and sediment in the Yellow River Basin has dropped drastically. This paper selected 125 rainfall and flood data points from 1965 to 2015, combined hydrological methods and mathematical statistics to analyze the hydrological factors and runoff generation mechanism, and combined the underlying surface conditions of the Gushanchuan Basin. The characteristics of change revealed the temporal and spatial variation characteristics and related factors of the runoff generation mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This would then lead to the gradual accumulation in the upper soil layers, forming a transient perched water table and, eventually, resulting in Dunne overland flow (Figures 6, 7). Several studies by hierarchical conceptual models also indicated this potential pattern of soil water redistribution (Ghimire et al, 2013; Hong, 2020; Tian et al, 2017; Zwartendijk et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This would then lead to the gradual accumulation in the upper soil layers, forming a transient perched water table and, eventually, resulting in Dunne overland flow (Figures 6, 7). Several studies by hierarchical conceptual models also indicated this potential pattern of soil water redistribution (Ghimire et al, 2013; Hong, 2020; Tian et al, 2017; Zwartendijk et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…The spatial resolution of the surface mesh varies gradually from 150 m near the catchment edges to 5 m along the channels and outlet. Given that the active hydrological processes within the vadose zone of the Loess Plateau are mainly within the shallow root zone (e.g., 0–1 m) (Suo et al, 2018), in this work the vertical soil depth was restricted to 10 m, which was sufficient for detecting the shallow hydrological response at short‐duration event scale and to better realize simulation convergence (Hong, 2020; Ran et al, 2019). The top one‐meter soil depth was divided into 10 sublayers with a vertical spacing of 0.1 m. For the soil depth at 1–2 m, the vertical spacing is 0.2 m, with a 1‐m spacing for the lower 2–10 m soil depth. Boundary conditions and initial conditions …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rigid vegetation, being less dense, is only a direct obstruction against rainfall impact on the land's surface, providing limited resistance. In contrast, flexible vegetation has shown more resistance, as surface runoff is continuously facing resistance in its path [27]. The combination of both rigid and flexible vegetation results in a collaborative resistance against surface runoff, making this mixed approach the most efficient.…”
Section: Introductionmentioning
confidence: 99%